Determinants of Economic Growth in the South Sumatra Region: Analysis of Labor Force Participation Rate, Human Development Index, and Population Growth from an Islamic Economic Perspective - Ridho Fahmi; Budimansyah; Yulistia Devi (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study aims to analyze the influence of the Labor Force Participation Rate (TPAK), Human Development Index (HDI), and population growth on economic growth in the Southern Sumatra region, which includes the provinces of Lampung, South Sumatra, Jambi, Bengkulu, and the Bangka Belitung Islands during the period 2015–2024. Methodology: This study uses a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS), the Inter-Provincial Central Statistics Agency (BPS) in the South Sumatra and South Sumatra regions, and other official sources. The analysis technique used involves several stages, namely the Chow Test, the Hausman Test, and the Lagrange Multiplier Test. This is followed by Assumption Testing and Hypothesis Testing. Findings: The results of this study indicate that increased labor force participation and human development are related to increased economic growth. This research can simultaneously have a significant impact in explaining regional economic conditions. A gap in this research is the limited number of studies that discuss the interrelationships between these research variables using a panel data approach. This research is expected to contribute to the development of regional economic studies and Islamic economics to support equitable and sustainable economic growth.